Mediterranean semi-arid plant Astragalus armatus as a source of bioactive galactomannan. Issue 1 (January 2015) - Boual, Zakaria; Pierre, Guillaume; Delattre, Cédric; Benaoun, Fatima; Petit, Emmanuel; Gardarin, Christine; Michaud, Philippe; El Hadj, Mohamed Didi Ould
Abstract A water-soluble polysaccharide fraction (WSPF) was extracted and purified from Astragalus armatus Lam. (Fabaceae), a spontaneous plant found in North Algerian Sahara. The structural features of WSPF were evaluated by colorimetric assays, Fourier transform infrared (FTIR) spectroscopy, high performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) and gas chromatography coupled to mass spectrometry (GC/MS). WSPF was a galactomannan-rich fraction, with a β-(1, 4)-d-manp backbone with α-(1, 6)-d-galp branches, and a Man:Gal ratio of 1.13. Besides, the anti-complement activity and the antioxidant potential (DPPH and hydroxyl radicals) of WSPF were evaluated. The results exhibited an anti-complementary activity, with an IC50 value of 0.39 mg/mL of the fraction, better than for heparin (0.58 mg/mL). Moreover, WSPF possessed a notable antioxidant activity on DPPH radical with an IC50 of 330 µg/mL.